2011
DOI: 10.1002/hbm.21331
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of crossmodal reorganization of the voice area in cochlear‐implanted deaf patients

Abstract: Psychophysical and neuroimaging studies in both animal and human subjects have clearly demonstrated that cortical plasticity following sensory deprivation leads to a brain functional reorganization that favors the spared modalities. In postlingually deaf patients, the use of a cochlear implant (CI) allows a recovery of the auditory function, which will probably counteract the cortical crossmodal reorganization induced by hearing loss. To study the dynamics of such reversed crossmodal plasticity, we designed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
91
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 45 publications
9
91
1
2
Order By: Relevance
“…A significant reduction in cross-modal activation to visual speech has previously been documented from approximately 1 wk to 8 mo post-CI within anterior portions of the right superior temporal sulcus (9). Thus, we next examined changes in the amplitude of cross-modal activation to visual speech within the left and the right STC separately.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…A significant reduction in cross-modal activation to visual speech has previously been documented from approximately 1 wk to 8 mo post-CI within anterior portions of the right superior temporal sulcus (9). Thus, we next examined changes in the amplitude of cross-modal activation to visual speech within the left and the right STC separately.…”
Section: Resultsmentioning
confidence: 92%
“…Data pertaining to changes over time in activation of auditory brain regions by visual speech are not available from existing studies for both CI users and NH control subjects (9). We therefore asked whether the observed change over time in right STC activation to visual speech differed between CI users and NH controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the contribution of the visual cortex to speech recognition increased over time after implantation (Giraud et al 2001b), suggesting that the CI users were actively using enhanced audio-visual integration to facilitate their learning of the novel speech sounds received through the CI. In contrast, Rouger et al (2012) suggested a negative impact of cross modal plastic-ity: they found that the right temporal voice area (TVA) was abnormally activated in CI users by a visual speech-reading task and that this activity declined over time after implantation while the activity in Broca's area (normally activated by speech reading) increased over time after implantation. Coez et al (2008) also used PET to study activation by voice stimuli of the TVA in CI users with poor and good speech understanding.…”
Section: Deafness Language and Brain Plasticity: Evidence From Imagimentioning
confidence: 99%